2020
DOI: 10.1093/ejcts/ezaa439
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral mitochondrial dysfunction and reactive oxygen species with cardiopulmonary bypass

Abstract: OBJECTIVES Neurodevelopmental injury after cardiac surgery using cardiopulmonary bypass (CPB) for congenital heart defects is common, but the mechanism behind this injury is unclear. This study examines the impact of CPB on cerebral mitochondrial reactive oxygen species (ROS) generation and mitochondrial bioenergetics. METHODS Twenty-three piglets (mean weight 4.2 ± 0.5 kg) were placed on CPB for either 1, 2, 3 or 4 h (n = 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The finding of increased Lac during DHCA was consistent with previous reports of high Lac levels as measured by microdialysis 44 ; however, the dynamic MRS measurements also permitted measurement of both the Lac production rate and Lac/Glc ratios. Although reduction of brain glucose and increase of Lac were generally consistent with previous DHCA studies, 44 we observed a large deviation during CA from the stoichiometric predicted glycolytic value of ΔLac/ΔGlc of 2, whereby, under anaerobic conditions, each Glu molecule should generate two Lac molecules.…”
Section: Discussionsupporting
confidence: 90%
“…The finding of increased Lac during DHCA was consistent with previous reports of high Lac levels as measured by microdialysis 44 ; however, the dynamic MRS measurements also permitted measurement of both the Lac production rate and Lac/Glc ratios. Although reduction of brain glucose and increase of Lac were generally consistent with previous DHCA studies, 44 we observed a large deviation during CA from the stoichiometric predicted glycolytic value of ΔLac/ΔGlc of 2, whereby, under anaerobic conditions, each Glu molecule should generate two Lac molecules.…”
Section: Discussionsupporting
confidence: 90%
“…Therapies that target various aspects of mitochondrial function and ROS production have been shown to decrease synaptic plasticity, improve communication deficits, and motor impairments in patients with congenital mitochondrial deficits 31 and thus may represent a potential focal point for future interventions in children with CHD. Furthermore, how complex I adapts to additional stressors such a cardiopulmonary bypass 32 or sudden increase in oxygen tension in the brain postpartum, either during mechanical ventilation and perioperative, is a critical knowledge gap, as increased oxygen tension postoperatively could provide more cellular fuel for ROS production following conformational dynamic changes of complex I discovered in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that the damage caused by oxidative stress is mediated by reactive oxygen species which plays an important role in neurodegenerative diseases [ 20 , 21 ]. H 2 O 2 produced in the body during metabolism is equivalent to reactive oxygen species and can aggravate the body oxidative stress injury [ 22 , 23 ]. The results of this study showed that H 2 O 2 induced oxidative damage and apoptosis in RLE-6TN cells which was reduced by 4,7-didehydro-neophysalin B treatment as shown in Figure 2(c) .…”
Section: Discussionmentioning
confidence: 99%